Internal dynamics of multidomain protein as revealed by an optimized neutron spin echo measurement and all-atom molecular dynamics simulation - Rintaro Inoue; Tomotaka Oroguchi; Takashi Oda; Bela Farago; Anne Martel; Lionel Porcar; Mamoru Sato; Masaaki Sugiyama (Physical Review Research, 2023)
Identification of the internal dynamics of multidomain proteins is crucial for clarifying the mechanism of their functions. The neutron spin echo (NSE) technique is well suited for studying internal dynamics. However, the requirement for relatively high protein concentrations and the lack of appropriate analytical methods have impeded the investigation of the internal dynamics with NSE. To overcome these difficulties, we employed a unique approach to study the internal dynamics of a multidomain protein, EcoO109I, whose dynamics was anticipated to be pertinent to DNA degradation. We anticipated a synergetic effect between the NSE measurement at interference-free protein concentration and all-atom molecular dynamics simulation. Through this approach, the internal dynamics of EcoO109I was successfully observed within temporal and spatial scales. Additionally, principal component analysis (PCA) was applied to the internal dynamics trajectory to identify the dominant motion of the internal dynamics. The first PCA mode, which was the most cooperative among all PCA modes, mainly explained the internal dynamics. This dominant mode of EcoO109I exhibited the motion which facilitated both the access of DNA to the recognition site and the cleavage of DNA. Therefore, our approach can identify the functionally relevant internal dynamics of multidomain proteins.